ChemInform Abstract: Asymmetric Synthesis of N‐Stereogenic Molecules: Diastereoselective Double Aza‐Michael Reaction. Issue 21 (27th May 2014) - Lauber, Alex; Zelenay, Benjamin; Cvengros, Jan
Abstract A rare example of stereoselective synthesis of molecules possessing configurationally stable chirogenic nitrogen atoms is developed.